Nanometer TiCoMoCrNi / Cr composite structure coating with diffusion resistance and oxidation resistance and preparation method of nanometer TiCoMoCrNi / Cr composite structure coating

By designing nano-TiCoMoCrNi/Cr composite structural coating on the surface of zirconium alloy matrix, the structural defects of existing Cr oxidation-resistant coatings and interdiffusion of substrate and coating at high temperatures are solved, and better high-temperature oxidation resistance and Security.

CN119491187APending Publication Date: 2025-02-21NORTHWEST INSTITUTE FOR NONFERROUS METAL RESEARCH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411610944.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing Cr antioxidant coatings are prone to structural defects such as cracks and holes at high temperatures, and the interdiffusion problem between the substrate and the coating is difficult to effectively solve, which limits its application in the field of nuclear power.

Method used

Design the nano-TiCoMoCrNi/Cr composite structural coating, and by depositing the TiCoMoCrNi diffusion barrier layer as the inner layer on the surface of the zirconium alloy matrix, and depositing the Cr antioxidant coating on the outer layer, forming a composite structural coating, improving the film-based binding performance and preventing the matrix from being combined with the Inter-diffusion between coating elements.

Benefits of technology

Effectively prevents interdiffusion between the substrate and the coating elements, protects the substrate, and significantly improves the coating's high-temperature oxidation resistance. It is suitable for complex working conditions in the nuclear power field, and enhances the safety and reliability of fuel cladding materials. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119491187A_ABST
    Figure CN119491187A_ABST
Patent Text Reader

Abstract

The invention discloses a nano TiCoMoCrNi / Cr composite structure coating with both diffusion resistance and oxidation resistance. The nano TiCoMoCrNi / Cr composite structure coating comprises a TiCoMoCrNi diffusion barrier layer on the inner layer and a Cr oxidation-resistant coating on the outer layer, wherein the TiCoMoCrNi diffusion barrier layer and the Cr oxidation-resistant coating are located on the surface of a base body. The preparation method of the coating comprises the following steps: 1, pretreating the substrate; 2, ion source cleaning; 3, preparing a diffusion barrier layer; and 4, preparing the Cr anti-oxidation coating. The nano high-entropy alloy TiCoMoCrNi layer is designed between the base body and the Cr anti-oxidation coating to serve as a diffusion barrier layer, film-base combination between the base body and the coating is improved, mutual diffusion between the base body and coating elements is prevented, and therefore the service safety and reliability of the composite structure coating under the working condition of a water loss accident are guaranteed and improved; according to the method, the physical vapor deposition method is adopted, so that the coating and the matrix have good metallurgical bonding, the structure distribution is uniform and flawless, the oxidation resistance of the coating on the surface of the fuel cladding is improved, and the method is suitable for the nuclear power field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of pressurized water reactor fuel cladding coatings, and in particular relates to a nano TiCoMoCrNi / Cr composite structure coating that takes both diffusion resistance and oxidation resistance into consideration and a preparation method thereof. Background Art

[0002] In order to cope with global extreme climate change, the development of a low-carbon economy has become the main direction. Against the backdrop of the booming global low-carbon economy, it is necessary to develop nuclear energy safely and efficiently, promote the clean energy structure of China, and inject new impetus into the green transformation. At present, the research and development of new materials and the practical development of research and development results are key issues restricting the rapid development of the energy industry, and play a guiding role in improving energy efficiency and reducing emissions in traditional industries.

[0003] Focusing on the demand for fuel cladding materials in the nuclear power field, the material's resistance to high-temperature steam oxidation is a key factor in ensuring the safe and reliable operation of nuclear reactors. Among the coatings currently used for zirconium alloy surface protection, metal Cr anti-oxidation coatings are considered to be the most valuable coating system for fuel cladding. The preparation process of Cr anti-oxidation coatings adopts the method of physical vapor deposition. Most of the coatings will grow in a columnar coarse crystal structure. The existing intercrystalline gaps provide channels for the diffusion of atoms, which not only promotes the mutual diffusion between the coating and the matrix elements, but also makes the coating prone to structural defects such as cracks and holes at high temperatures. In the existing accident-resistant fuel coating system, composite coatings are often used to make up for the structural defects of single coatings, but the mutual compatibility, thermal expansion coefficient and high-temperature stability differences between the coating materials are key factors limiting their application.

[0004] Therefore, in view of the limitations of the existing Cr anti-oxidation coating structure and preparation process, it is necessary to provide a nano-TiCoMoCrNi / Cr composite structure coating and a preparation method thereof that takes both diffusion resistance and oxidation resistance into consideration. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a nano TiCoMoCrNi / Cr composite structure coating that takes both diffusion resistance and oxidation resistance into consideration in view of the deficiencies of the above-mentioned prior art. The coating forms a composite structure coating by designing a nano high entropy alloy TiCoMoCrNi layer between the substrate and the Cr oxidation resistance coating as a diffusion barrier layer, thereby improving the film-substrate bonding performance between the substrate and the coating, effectively preventing the mutual diffusion between the substrate and the coating elements, thereby protecting the substrate, and the coating exhibits excellent high-temperature oxidation resistance, is suitable for complex working conditions in the nuclear power field, and solves the mutual diffusion problem between the coating and the substrate of the pressurized water reactor fuel cladding material.

[0006] To solve the above technical problems, the technical solution adopted by the present invention is: a nano TiCoMoCrNi / Cr composite structural coating that takes into account both diffusion resistance and oxidation resistance, characterized in that it includes an inner TiCoMoCrNi diffusion barrier layer located on the surface of a zirconium alloy substrate and an outer Cr oxidation resistance coating, and the mass percentages of Ti, Co, Mo, Cr, and Ni components in the TiCoMoCrNi diffusion barrier layer are: 15.0% to 16.0%, 18.5% to 19.0%, 30.0% to 31.0%, 16.3% to 16.6%, and 18.5% to 19.0%.

[0007] The present invention designs a nano TiCoMoCrNi / Cr composite structure coating on the surface of a substrate, wherein TiCoMoCrNi is used as a diffusion barrier layer located in the inner layer of the substrate surface, the diffusion barrier layer is composed of Ti, Co, Mo, Cr and Ni elements, and has excellent high temperature oxidation resistance, and the Mo element can cause lattice distortion, effectively improving the coating's resistance to dislocation movement, thereby improving the coating's hardness and yield strength, Ni and Cr have strong corrosion resistance, improve the coating's corrosion resistance, and slow down the damage to the substrate caused by coating failure; At the same time, the TiCoMoCrNi diffusion barrier layer has a dense microstructure, without loose structural defects such as holes and cracks, which effectively blocks the mutual diffusion of elements, especially Zr-Cr, between the substrate and the outer Cr anti-oxidation coating on its surface, reduces the diffusion of oxygen elements into the substrate, thereby protecting the substrate, and increasing the bonding strength between the coating and the substrate, ensuring the protective effect of the coating; in addition, the high-entropy alloy TiCoMoCrNi diffusion barrier layer has good thermal stability, good thermal matching with the substrate and the outer Cr anti-oxidation coating, and reduces the occurrence of structural defects such as cracks and holes.

[0008] The above-mentioned nano-TiCoMoCrNi / Cr composite structure coating that takes into account both diffusion resistance and oxidation resistance is characterized in that the microstructure of the TiCoMoCrNi / Cr composite structure coating is composed of uniform and fine nano-grains, the thickness of the TiCoMoCrNi diffusion barrier layer is 600nm-850nm, and the thickness of the Cr oxidation resistance coating is 6μm-8μm. By controlling the microstructure of the TiCoMoCrNi / Cr composite structure coating to be composed of uniform and fine nano-grains, the hardness and wear resistance of the coating can be further improved; by limiting the thickness of the TiCoMoCrNi diffusion barrier layer and the Cr oxidation resistance coating, the internal stress of the coating is reduced while ensuring the coating performance.

[0009] At the same time, the present invention also discloses a method for preparing the above-mentioned nano TiCoMoCrNi / Cr composite structure coating that takes both diffusion resistance and oxidation resistance into consideration, characterized in that the method comprises the following steps:

[0010] Step 1: pretreatment of substrate: pickling, grinding, polishing and ultrasonic cleaning are performed on the substrate in sequence to obtain a pretreated substrate;

[0011] Step 2, ion source cleaning: fix the pretreated substrate obtained in step 1 on the sample stage of the equipment vacuum chamber, place the TiCoMoCrNi target on the target position in the center of the sputtering source, determine the position of the substrate and the TiCoMoCrNi target, start the ion source cleaning of the substrate, and start the heater to heat the substrate;

[0012] Step 3, preparation of TiCoMoCrNi diffusion barrier layer: using Ar gas as sputtering gas, using DC magnetron sputtering, depositing and preparing TiCoMoCrNi diffusion barrier layer on the surface of the substrate heated in step 2;

[0013] Step 4: Preparation of Cr anti-oxidation coating: Fix the Cr target on the target position, use Ar gas as the sputtering gas, perform ion source cleaning on the substrate with the TiCoMoCrNi diffusion barrier layer on the surface in step 3, and then use multi-arc ion plating to deposit the Cr anti-oxidation coating to obtain a nano TiCoMoCrNi / Cr composite structure coating.

[0014] Generally, the substrate or substrate used in the present invention is a zirconium alloy, preferably a Zr-4 alloy; the pickling solution used in the pickling in step 1 is prepared by 16 mol / L concentrated HNO3, 33.3 mol / L HF acid and deionized water in a volume ratio of 45:5:50, and the pickling time is 55 s; the grinding is performed step by step using 800#, 1000#, 1200# and 2000# sandpaper in sequence; the polishing is performed on a polishing machine using a diamond polishing paste with a particle size of 1.5 μm; the ultrasonic cleaning time is 30 min, followed by drying with an air gun for standby use.

[0015] The above method is characterized in that the ion source cleaning time in step 2 is 15 minutes to 20 minutes.

[0016] The above method is characterized in that the vacuum degree of the ion source cleaning in step 2 is 1×10 -3 Pa, and introduce Ar gas into the vacuum chamber with a flow rate of 45 mL / min to 60 mL / min.

[0017] The above method is characterized in that the heating temperature of the substrate in step 2 is 200°C to 230°C.

[0018] The above method is characterized in that the target-substrate distance between the substrate and the TiCoMoCrNi target in step 2 is 8 cm to 10 cm.

[0019] The above method is characterized in that the vacuum degree of DC magnetron sputtering in step 3 is 1×10 -3 Pa~1×10 -4 Pa, working pressure is 1.0×10 -1 Pa~3.0×10 -1 Pa, the inert gas flow rate is 30mL / min~50mL / min, the transmission speed is 2m / min~4m / min, the sputtering power is 80W~120W, the bias voltage is -60V~-80V, and the sputtering time is 15min~30min.

[0020] The above method is characterized in that the ion source cleaning in step 4 includes two stages: glow ion cleaning and metal ion cleaning: when the vacuum degree in the vacuum chamber reaches 5×10 -2 Pa, turn on the heating system to heat the substrate to 220℃~280℃, then introduce Ar gas into the vacuum chamber to adjust the vacuum degree to 1Pa, and the Ar gas flow rate is 80mL / min~100mL / min, then turn on and adjust the bias power supply to 1200V for glow ion cleaning for 3min; after the glow ion cleaning is completed, reduce the Ar gas flow rate to adjust the vacuum degree to 0.1Pa, and reduce the bias value to 800V for metal ion cleaning for 1min.

[0021] The above method is characterized in that the deposition target current of the multi-arc ion plating in step 4 is 60A to 100A, the bias voltage is 260V to 350V, the deposition pressure is 0.5Pa to 2Pa, and the deposition time is 8h to 10h.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] 1. The present invention adopts a physical vapor deposition method to prepare a nano-sized high-entropy alloy TiCoMoCrNi diffusion barrier layer structure, and improves the strength of the high-entropy alloy, especially the yield strength, through fine grain strengthening. At the same time, the addition of Ti element increases the strength and elongation of the high-entropy alloy, and produces a high-density dislocation in the high-entropy alloy, further hindering the dislocation movement. The large atomic radius of the Mo element will produce solid solution strengthening, so that the high-entropy alloy has a stable single-phase solid solution structure, thereby improving the performance of the high-entropy alloy TiCoMoCrNi diffusion barrier layer through the synergistic effect of fine grain strengthening and solid solution strengthening, and exhibiting excellent high-temperature oxidation resistance, thereby improving the safety and reliability of the composite structure coating in service under dehydration accident conditions, and solving the problem that the Cr / Zr interface diffusion affects the stability of the coating. The present invention can be used as a candidate material for the accident-resistant fuel coating on the surface of zirconium alloy.

[0024] 2. The present invention obtains a high-resistance coating with uniform thickness, few internal defects and good density by adjusting the preparation process parameters, such as changing the temperature, bias voltage, gas flow rate and deposition time, which effectively improves the problem of cracking and peeling of the coating at high temperature, and reduces the crack tendency of the oxide film.

[0025] 3. The present invention adopts a physical vapor deposition method to prepare a highly resistant nano-TiCoMoCrNi / Cr composite structure coating on the surface of a zirconium alloy substrate. The coating has good bonding with the substrate, is evenly distributed in the structure, and has no obvious defects such as cracks and pores. The prepared nano-TiCoMoCrNi diffusion barrier layer can effectively prevent the mutual diffusion between the substrate and the coating elements. The nano-TiCoMoCrNi / Cr composite structure coating after high-temperature steam oxidation experiment has better antioxidant properties than the Cr coating.

[0026] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a microscopic morphology of the nano-TiCoMoCrNi diffusion barrier layer prepared in Example 3 of the present invention.

[0028] Figure 2 This is a cross-sectional morphology diagram and element distribution curve diagram of the nano-TiCoMoCrNi / Cr composite structure coating prepared in Example 3 of the present invention.

[0029] Figure 3 This is a surface morphology of the nano-TiCoMoCrNi / Cr composite structure coating prepared in Example 3 of the present invention after high-temperature air oxidation at 1200°C for 1 hour.

[0030] Figure 4 This is an oxygen weight gain curve of the nano-TiCoMoCrNi / Cr composite structure coating prepared in Example 3 of the present invention and the Cr coating prepared in Comparative Example 1 after being oxidized in high-temperature air for 1 hour. DETAILED DESCRIPTION

[0031] Example 1

[0032] The nano TiCoMoCrNi / Cr composite structural coating that takes both diffusion resistance and oxidation resistance into consideration in this embodiment comprises an inner TiCoMoCrNi diffusion barrier layer and an outer Cr oxidation resistance coating located on the surface of a Zr-4 substrate, wherein the thickness of the TiCoMoCrNi diffusion barrier layer is 850 nm, the thickness of the Cr oxidation resistance coating is 8 μm, and the mass percentages of Ti, Co, Mo, Cr, and Ni components in the TiCoMoCrNi diffusion barrier layer are 15.0%, 18.5%, 31.0%, 16.5%, and 19.0%, respectively. The microstructure of the TiCoMoCrNi / Cr composite structural coating is composed of uniform and fine nano-grains.

[0033] The preparation method of the nano TiCoMoCrNi / Cr composite structure coating that takes both diffusion resistance and oxidation resistance into consideration in this embodiment comprises the following steps:

[0034] Step 1, substrate pretreatment: The Zr-4 substrate is pickled, ground, polished and ultrasonically cleaned in sequence to obtain a pretreated substrate; the pickling solution used for pickling is prepared by 16 mol / L concentrated HNO3, 33.3 mol / L HF acid and deionized water in a volume ratio of 45:5:50, and the pickling time is 55 s. After the pickling is completed, 800#, 1000#, 1200#, and 2000# sandpaper are used in sequence for step-by-step grinding, and then a diamond polishing paste with a particle size of 1.5 μm is used for polishing on a polishing machine, and then ultrasonic cleaning is used for 30 minutes, followed by blowing dry with an air gun for standby use;

[0035] Step 2: Ion source cleaning: fix the pretreated Zr-4 substrate obtained in step 1 on the sample stage of the vacuum chamber of the equipment, place the TiCoMoCrNi target on the target position in the center of the sputtering source, and determine that the target-substrate distance between the Zr-4 substrate and the TiCoMoCrNi target is 8 cm. Start ion pairing to clean the Zr-4 substrate with the ion source for 15 min. The vacuum degree of the ion source cleaning is 1×10 -3 Pa, and Ar gas was introduced into the vacuum chamber at a flow rate of 45 mL / min, and the heater was started to heat the Zr-4 substrate to 200 °C;

[0036] Step 3: Preparation of TiCoMoCrNi diffusion barrier layer: Ar gas was used as sputtering gas, DC magnetron sputtering was adopted, and the vacuum degree was adjusted to 1×10 -3 Pa, working pressure is 1.0×10 -1 Pa, the inert gas flow rate is 30mL / min, the transmission speed is 2m / min, the sputtering power is 80W, the bias voltage is -60V, and the sputtering time is 15min. The TiCoMoCrNi diffusion barrier layer is deposited on the surface of the Zr-4 substrate heated in step 2;

[0037] Step 4: Preparation of Cr anti-oxidation coating: Fix a Cr target with a mass purity of 99.99% on the target position, use Ar gas as the sputtering gas, adjust the target-substrate distance between the Zr-4 substrate with a TiCoMoCrNi diffusion barrier layer on the surface and the Cr target to 20 cm, and perform ion source cleaning on the Zr-4 substrate with a TiCoMoCrNi diffusion barrier layer on the surface: wait until the vacuum degree in the vacuum chamber reaches 5×10 -2 Pa, start the heating system, heat the Zr-4 substrate with a TiCoMoCrNi diffusion barrier layer on the surface to 220°C, then introduce Ar gas into the vacuum chamber to adjust the vacuum degree to 1Pa, the Ar gas flow rate is 80mL / min, then turn on and adjust the bias power supply to 1200V for glow ion cleaning for 3min; after the glow ion cleaning is completed, reduce the Ar gas flow rate to adjust the vacuum degree to 0.1Pa, and reduce the bias value to 800V for metal ion cleaning for 1min; after the ion source cleaning is completed, multi-arc ion plating is used to deposit a Cr anti-oxidation coating on the Zr-4 substrate with a TiCoMoCrNi diffusion barrier layer on the surface, the deposition target current is 60A, the bias voltage is 260V, the deposition pressure is 0.5Pa, and the deposition time is 8h to obtain a nano TiCoMoCrNi / Cr composite structure coating.

[0038] The results show that the oxidation rate of the nano-TiCoMoCrNi / Cr composite structure coating prepared in this embodiment after being oxidized in air at 1200°C for 1 hour is 0.39 mg / cm 2 .

[0039] Example 2

[0040] The nano TiCoMoCrNi / Cr composite structural coating that takes into account both diffusion resistance and oxidation resistance in this embodiment includes an inner TiCoMoCrNi diffusion barrier layer and an outer Cr oxidation resistance coating located on the surface of the Zr-4 substrate, and the thickness of the TiCoMoCrNi diffusion barrier layer is 750nm, the thickness of the Cr oxidation resistance coating is 8μm, and the mass percentages of Ti, Co, Mo, Cr, and Ni components in the TiCoMoCrNi diffusion barrier layer are: 16.0%, 19.0%, 30.0%, 16.5%, and 18.5%. The microstructure of the TiCoMoCrNi / Cr composite structural coating is composed of uniform and fine nano-grains.

[0041] The preparation method of the nano TiCoMoCrNi / Cr composite structure coating that takes both diffusion resistance and oxidation resistance into consideration in this embodiment comprises the following steps:

[0042] Step 1, substrate pretreatment: The Zr-4 substrate is pickled, ground, polished and ultrasonically cleaned in sequence to obtain a pretreated substrate; the pickling solution used for pickling is prepared by 16 mol / L concentrated HNO3, 33.3 mol / L HF acid and deionized water in a volume ratio of 45:5:50, and the pickling time is 55 s. After the pickling is completed, 800#, 1000#, 1200#, and 2000# sandpaper are used in sequence for step-by-step grinding, and then a diamond polishing paste with a particle size of 1.5 μm is used for polishing on a polishing machine, and then ultrasonic cleaning is used for 30 minutes, followed by blowing dry with an air gun for standby use;

[0043] Step 2: Ion source cleaning: fix the pretreated Zr-4 substrate obtained in step 1 on the sample stage of the vacuum chamber of the equipment, place the TiCoMoCrNi target on the target position in the center of the sputtering source, and determine that the target-substrate distance between the Zr-4 substrate and the TiCoMoCrNi target is 10 cm. Start the ion pair to clean the Zr-4 substrate with the ion source for 10 minutes. The vacuum degree of the ion source cleaning is 1×10 -3 Pa, and Ar gas was introduced into the vacuum chamber at a flow rate of 60 mL / min, and the heater was started to heat the Zr-4 substrate to 200 °C;

[0044] Step 3: Preparation of TiCoMoCrNi diffusion barrier layer: Ar gas was used as sputtering gas, DC magnetron sputtering was adopted, and the vacuum degree was adjusted to 1×10 -3 Pa, working pressure is 3.0×10 -1 Pa, the inert gas flow rate is 50mL / min, the transmission speed is 4m / min, the sputtering power is 80W, the bias voltage is -70V, and the sputtering time is 20min. The TiCoMoCrNi diffusion barrier layer is deposited on the surface of the Zr-4 substrate heated in step 2;

[0045] Step 4: Preparation of Cr anti-oxidation coating: Fix a Cr target with a mass purity of 99.99% on the target position, use Ar gas as the sputtering gas, adjust the target-substrate distance between the Zr-4 substrate with a TiCoMoCrNi diffusion barrier layer on the surface and the Cr target to 20 cm, and perform ion source cleaning on the Zr-4 substrate with a TiCoMoCrNi diffusion barrier layer on the surface: wait until the vacuum degree in the vacuum chamber reaches 5×10 -2Pa, start the heating system, heat the Zr-4 substrate with a TiCoMoCrNi diffusion barrier layer on the surface to 260°C, then introduce Ar gas into the vacuum chamber to adjust the vacuum degree to 1Pa, the Ar gas flow rate is 80mL / min, then turn on and adjust the bias power supply to 1200V for glow ion cleaning for 3min; after the glow ion cleaning is completed, reduce the Ar gas flow rate to adjust the vacuum degree to 0.1Pa, and reduce the bias value to 800V for metal ion cleaning for 1min; after the ion source cleaning is completed, multi-arc ion plating is used to deposit a Cr anti-oxidation coating on the Zr-4 substrate with a TiCoMoCrNi diffusion barrier layer on the surface, the deposition target current is 80A, the bias voltage is 300V, the deposition pressure is 2Pa, and the deposition time is 10h to obtain a nano TiCoMoCrNi / Cr composite structure coating.

[0046] The results show that the oxidation rate of the nano-TiCoMoCrNi / Cr composite structure coating prepared in this embodiment after being oxidized in air at 1200°C for 1 hour is 0.28 mg / cm 2 .

[0047] Example 3

[0048] The nano TiCoMoCrNi / Cr composite structural coating that takes into account both diffusion resistance and oxidation resistance in this embodiment includes an inner TiCoMoCrNi diffusion barrier layer and an outer Cr oxidation resistance coating located on the surface of the Zr-4 substrate, and the thickness of the TiCoMoCrNi diffusion barrier layer is 600nm, the thickness of the Cr oxidation resistance coating is 6μm, and the mass percentages of Ti, Co, Mo, Cr, and Ni components in the TiCoMoCrNi diffusion barrier layer are: 15.28%, 18.79%, 30.57%, 16.56%, and 18.79%. The microstructure of the TiCoMoCrNi / Cr composite structural coating is composed of uniform and fine nano-grains.

[0049] The preparation method of the nano TiCoMoCrNi / Cr composite structure coating that takes both diffusion resistance and oxidation resistance into consideration in this embodiment comprises the following steps:

[0050] Step 1, substrate pretreatment: The Zr-4 substrate is pickled, ground, polished and ultrasonically cleaned in sequence to obtain a pretreated substrate; the pickling solution used for pickling is prepared by 16 mol / L concentrated HNO3, 33.3 mol / L HF acid and deionized water in a volume ratio of 45:5:50, and the pickling time is 55 s. After the pickling is completed, 800#, 1000#, 1200#, and 2000# sandpaper are used in sequence for step-by-step grinding, and then a diamond polishing paste with a particle size of 1.5 μm is used for polishing on a polishing machine, and then ultrasonic cleaning is used for 30 minutes, followed by blowing dry with an air gun for standby use;

[0051] Step 2: Ion source cleaning: fix the pretreated Zr-4 substrate obtained in step 1 on the sample stage of the vacuum chamber of the equipment, place the TiCoMoCrNi target on the target position in the center of the sputtering source, and determine that the target-substrate distance between the Zr-4 substrate and the TiCoMoCrNi target is 10 cm. Start ion pairing to clean the Zr-4 substrate with the ion source for 20 minutes. The vacuum degree of the ion source cleaning is 1×10 -3 Pa, and Ar gas was introduced into the vacuum chamber at a flow rate of 60 mL / min, and the heater was started to heat the Zr-4 substrate to 230 °C;

[0052] Step 3: Preparation of TiCoMoCrNi diffusion barrier layer: Ar gas was used as sputtering gas, DC magnetron sputtering was adopted, and the vacuum degree was adjusted to 1×10 -4 Pa, working pressure is 3.0×10 -1 Pa, the inert gas flow rate is 50mL / min, the transmission speed is 4m / min, the sputtering power is 120W, the bias voltage is -200V, and the sputtering time is 30min. The TiCoMoCrNi diffusion barrier layer is deposited on the surface of the Zr-4 substrate heated in step 2;

[0053] Step 4: Preparation of Cr anti-oxidation coating: Fix a Cr target with a mass purity of 99.99% on the target position, use Ar gas as the sputtering gas, adjust the target-substrate distance between the Zr-4 substrate with a TiCoMoCrNi diffusion barrier layer on the surface and the Cr target to 20 cm, and perform ion source cleaning on the Zr-4 substrate with a TiCoMoCrNi diffusion barrier layer on the surface: wait until the vacuum degree in the vacuum chamber reaches 5×10 -2 Pa, start the heating system, heat the Zr-4 substrate with a TiCoMoCrNi diffusion barrier layer on the surface to 280°C, then introduce Ar gas into the vacuum chamber to adjust the vacuum degree to 1Pa, the Ar gas flow rate is 100mL / min, then turn on and adjust the bias power supply to 1200V for glow ion cleaning for 3min; after the glow ion cleaning is completed, reduce the Ar gas flow rate to adjust the vacuum degree to 0.1Pa, and reduce the bias value to 800V for metal ion cleaning for 1min; after the ion source cleaning is completed, multi-arc ion plating is used to deposit a Cr anti-oxidation coating on the Zr-4 substrate with a TiCoMoCrNi diffusion barrier layer on the surface, the deposition target current is 100A, the bias voltage is 350V, the deposition pressure is 1Pa, and the deposition time is 8h to obtain a nano TiCoMoCrNi / Cr composite structure coating.

[0054] The results show that the oxidation rate of the nano-TiCoMoCrNi / Cr composite structure coating prepared in this embodiment after being oxidized in air at 1200°C for 1 hour is 0.13 mg / cm 2 .

[0055] Figure 1 This is the microscopic morphology of the TiCoMoCrNi diffusion barrier layer prepared in this embodiment. Figure 1 It can be seen that the surface of the TiCoMoCrNi diffusion barrier layer is smooth and dense, and has no obvious hole defects.

[0056] Figure 2 The cross-sectional morphology and element distribution curve of the nano-TiCoMoCrNi / Cr composite structure coating prepared in this embodiment are shown in FIG. Figure 2 The horizontal axis of the element distribution curve is the distance from the matrix. Figure 2 It can be seen that the TiCoMoCrNi diffusion barrier layer in the nano-TiCoMoCrNi / Cr composite structure coating is tightly bonded to the substrate without obvious gaps and delamination, indicating that the TiCoMoCrNi diffusion barrier layer has good bonding with the substrate.

[0057] Figure 3 The surface morphology of the nano-TiCoMoCrNi / Cr composite structure coating prepared in this example after high-temperature air oxidation at 1200°C for 1 hour, where the right picture is an enlarged picture of the box part of the left picture. Figure 3 It can be seen that a dense oxide layer is formed on the surface of the nano-TiCoMoCrNi / Cr composite structure coating after high-temperature air oxidation.

[0058] Comparative Example 1

[0059] This comparative example is a Cr anti-oxidation coating on the surface of a Zr-4 substrate, with a thickness of 12.36 μm.

[0060] The preparation method of the Cr anti-oxidation coating of this comparative example comprises the following steps:

[0061] Step 1, substrate pretreatment: The Zr-4 substrate is pickled, ground, polished and ultrasonically cleaned in sequence to obtain a pretreated substrate; the pickling solution used for pickling is prepared by 16 mol / L concentrated HNO3, 33.3 mol / L HF acid and deionized water in a volume ratio of 45:5:50, and the pickling time is 55 s. After the pickling is completed, 800#, 1000#, 1200#, and 2000# sandpaper are used in sequence for step-by-step grinding, and then a diamond polishing paste with a particle size of 1.5 μm is used for polishing on a polishing machine, and then ultrasonic cleaning is used for 30 minutes, followed by blowing dry with an air gun for standby use;

[0062] Step 2: Preparation of Cr anti-oxidation coating: The pretreated Zr-4 substrate obtained in step 1 is fixed on the sample stage of the vacuum chamber of the equipment, and the Cr target with a mass purity of 99.99% is fixed on the target position. Ar gas is used as the sputtering gas, and the target-substrate distance between the Zr-4 substrate and the Cr target is adjusted to 20 cm. The pretreated Zr-4 substrate is cleaned by ion source: when the vacuum degree in the vacuum chamber reaches 5×10 -2 Pa, turn on the heating system to heat the Zr-4 substrate to 280°C, then introduce Ar gas into the vacuum chamber to adjust the vacuum degree to 1Pa, the Ar gas flow rate is 100mL / min, then turn on and adjust the bias power supply to 1200V for glow ion cleaning for 3min; after the glow ion cleaning is completed, reduce the Ar gas flow rate to adjust the vacuum degree to 0.1Pa, and reduce the bias value to 800V for metal ion cleaning for 1min; after the ion source cleaning is completed, multi-arc ion plating is used to deposit a Cr anti-oxidation coating on the pretreated Zr-4 substrate, the deposition target current is 100A, the bias voltage is 350V, the deposition pressure is 1Pa, and the deposition time is 8h to obtain a Cr coating.

[0063] The oxidation rate of the Cr anti-oxidation coating prepared in this embodiment after being oxidized in air at 1200°C for 1 hour is 0.49 mg / cm 2 .

[0064] Figure 4 The oxygen weight gain curves of the nano-TiCoMoCrNi / Cr composite structure coating prepared in Example 3 of the present invention and the Cr coating prepared in Comparative Example 1 after being oxidized in high temperature air for 1 hour are shown in FIG. Figure 4 It can be seen that after being oxidized in high-temperature air at 1200°C for 1 hour, the oxidation rate of the nano-TiCoMoCrNi / Cr composite structural coating of Example 3 is reduced by 73% compared with the single Cr coating of Comparative Example 1, indicating that the oxidation resistance of the nano-TiCoMoCrNi / Cr composite structural coating of the present invention at 1200°C is better than that of the single Cr coating.

[0065] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A nano TiCoMoCrNi / Cr composite structure coating that takes both diffusion resistance and oxidation resistance into consideration, characterized in that: The invention comprises an inner TiCoMoCrNi diffusion barrier layer and an outer Cr oxidation resistant coating located on the surface of a zirconium alloy substrate, wherein the mass percentages of Ti, Co, Mo, Cr and Ni components in the TiCoMoCrNi diffusion barrier layer are 15.0% to 16.0%, 18.5% to 19.0%, 30.0% to 31.0%, 16.3% to 16.6% and 18.5% to 19.0%.

2. The nano-TiCoMoCrNi / Cr composite structure coating that takes both diffusion resistance and oxidation resistance into consideration according to claim 1, characterized in that: The microstructure of the TiCoMoCrNi / Cr composite structure coating is composed of uniform and fine nano-grains. The thickness of the TiCoMoCrNi diffusion barrier layer is 600nm-850nm, and the thickness of the Cr anti-oxidation coating is 6μm-8μm.

3. A method for preparing the nano TiCoMoCrNi / Cr composite structure coating that takes both diffusion resistance and oxidation resistance into consideration as claimed in claim 1 or 2, characterized in that: The method comprises the following steps: Step 1: pretreatment of substrate: pickling, grinding, polishing and ultrasonic cleaning are performed on the substrate in sequence to obtain a pretreated substrate; Step 2, ion source cleaning: fix the pretreated substrate obtained in step 1 on the sample stage of the equipment vacuum chamber, place the TiCoMoCrNi target on the target position in the center of the sputtering source, determine the position of the substrate and the TiCoMoCrNi target, start the ion source cleaning of the substrate, and start the heater to heat the substrate; Step 3, preparation of TiCoMoCrNi diffusion barrier layer: using Ar gas as sputtering gas, using DC magnetron sputtering, depositing and preparing TiCoMoCrNi diffusion barrier layer on the surface of the substrate heated in step 2; Step 4: Preparation of Cr anti-oxidation coating: Fix the Cr target on the target position, use Ar gas as the sputtering gas, perform ion source cleaning on the substrate with the TiCoMoCrNi diffusion barrier layer on the surface in step 3, and then use multi-arc ion plating to deposit the Cr anti-oxidation coating to obtain a nano TiCoMoCrNi / Cr composite structure coating.

4. The method according to claim 3, characterized in that The ion source cleaning time in step 2 is 15 min to 20 min.

5. The method according to claim 3, characterized in that: The vacuum degree of the ion source cleaning in step 2 is 1×10 -3 Pa, and introduce Ar gas into the vacuum chamber with a flow rate of 45 mL / min to 60 mL / min.

6. The method according to claim 3, characterized in that The heating temperature of the substrate in step 2 is 200°C to 230°C.

7. The method according to claim 3, characterized in that In step 2, the target-substrate distance between the substrate and the TiCoMoCrNi target material is 8 cm to 10 cm.

8. The method according to claim 3, characterized in that The vacuum degree of DC magnetron sputtering in step 3 is 1×10 -3 Pa~1×10 -4 Pa, working pressure is 1.0×10 -1 Pa~3.0×10 -1 Pa, the inert gas flow rate is 30mL / min~50mL / min, the transmission speed is 2m / min~4m / min, the sputtering power is 80W~120W, the bias voltage is -60V~-80V, and the sputtering time is 15min~30min.

9. The method according to claim 3, characterized in that: The ion source cleaning in step 4 includes two stages: glow ion cleaning and metal ion cleaning. When the vacuum degree in the vacuum chamber reaches 5×10 -2 Pa, turn on the heating system to heat the substrate to 220℃~280℃, then introduce Ar gas into the vacuum chamber to adjust the vacuum degree to 1Pa, and the Ar gas flow rate is 80mL / min~100mL / min, then turn on and adjust the bias power supply to 1200V for glow ion cleaning for 3min; after the glow ion cleaning is completed, reduce the Ar gas flow rate to adjust the vacuum degree to 0.1Pa, and reduce the bias value to 800V for metal ion cleaning for 1min.

10. The method according to claim 3, characterized in that The deposition target current of the multi-arc ion plating in step 4 is 60A-100A, the bias voltage is 260V-350V, the deposition pressure is 0.5Pa-2Pa, and the deposition time is 8h-10h.